1993
DOI: 10.1002/bscb.19931021105
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerism and rotamerism in 2‐methylamino‐, 2‐anilino‐, 2‐acetamido‐, and 2‐benzamido‐pyridines

Abstract: Quantum chemical (CNDO-CI-1) simulation and theoretical analysis of UV absorption spectra of 2-amino-, 2-methylamino-, 2-anilino-, 2-acetamido-, and 2-benzamido-pyridines were carried out. A comparison of results with experiment provided information on tautomerism and rotamerim in abovementioned compounds in solution. Contrary to some literature data 2-aminopyridine in solution exists in dimeric form of 2-pyridylamine. Also 2-methylaminopyridine in solution forms a similar dimer. 2-Anilinopyridine appears in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…DFT vibrational studies of 5-bromo-2-nitropyridine (Sundaraganesan et al 2005), pyridinium complexes (Tayyari et al 2010), and 2-chloro-5-bromopyridine (Hiremath et al 2010; Kishor and Bhoop 2013) were reported. Tautomerization and rotamerization of aminopyridines has been reported (Davoodnia et al 2011; Alkorta and Elguero 2002; Pietrzycki et al 1993). The vibration (IR and Raman) spectra of aminopyridines, methyl-substituted aminopyridines and hydrogen chlorides of aminopyridines had been determined experimentally by Spinner (Spinner 1962).…”
Section: Introductionmentioning
confidence: 97%
“…DFT vibrational studies of 5-bromo-2-nitropyridine (Sundaraganesan et al 2005), pyridinium complexes (Tayyari et al 2010), and 2-chloro-5-bromopyridine (Hiremath et al 2010; Kishor and Bhoop 2013) were reported. Tautomerization and rotamerization of aminopyridines has been reported (Davoodnia et al 2011; Alkorta and Elguero 2002; Pietrzycki et al 1993). The vibration (IR and Raman) spectra of aminopyridines, methyl-substituted aminopyridines and hydrogen chlorides of aminopyridines had been determined experimentally by Spinner (Spinner 1962).…”
Section: Introductionmentioning
confidence: 97%